Pengaruh Keterampilan terhadap Kualitas Kerja Bidan di Puskesmas Mampu Poned Kota Bandung - Ami Amelia; Sri Suwarsi (Lembaga Pengembangan Kinerja Dosen, 2024)
Maternal mortality rates reflect the risks faced by the mother during pregnancy and childbirth. The high rate of maternal death is likely to occur in high risk pregnant women that can not detected earlier. The role of Puskesmas as primary health care facilities and midwives as the spearhead of service, becomes important in this early detection. Therefore, researchers are interested in the effect of competence on the performance of midwives in maternal health services in Puskesmas Mampu PONED Bandung. To determine Competence of Midwives, The Performance of Midwives and to determine the effect of Competence on the Performance of the midwives in Puskesmas Mampu PONED Bandung. The type of this research is verificative analysis with cases study methods. The sampling method using a total sampling method (census). The entire population will be selected as sample that is midwives who work at Puskesmas Mampu PONED Bandung 77 midwive. After data is collected, the data distribution will be tested using the product moment correlation technique. Then the data will proceed with analysis that consists of two parts: a descriptive analysis and regression analysis. The result of correlation analysis, obtained a very strong relationship between the Performance and Competence of the Midwives (r = 0.972). Then from the regression analysis known that there is an influence on the Performance and Competency of the Midwives (t arithmetic = 35.802). Competence and Performance of midwives in Puskesmas Mampu PONED Bandung is good. There is also a very strong influence between the competence of midwives with performance significantly